Epifluorescent imaging study of the effect of anti-diabetic drug metformin on colorectal cancer cell lines in vitro. Issue 4 (2017) - Venkatasubramani, Priyadharshini; Sima, Chao; Hua, Jianping; Cypert, Milana; Bittner, Michael; Datta, Aniruddha
No abstract available